Evaluation of phytochemical and superoxide dismutase activities of Enhalus acoroides (L.f.) Royle from coastal waters of North Sulawesi, Indonesia - Menajang, Febry S. I. (Vet World, 2020)
BACKGROUND AND AIM: Seagrasses are an excellent and potential bioresource to discover new natural bioactive compounds such as antioxidants that have beneficial effects on health. Natural antioxidants have many functions in biological systems, primarily for defense against oxidation which produces free radicals in food, chemicals, and living systems. This study aimed to discover new natural antioxidant agents, Enhalus acoroides (L.f.) Royle was evaluated for phytochemical constituents and the antioxidant activity against superoxide dismutase (SOD) was assessed. MATERIALS AND METHODS: Sample specimens of E. acoroides (L.f.) Royle collected from two different areas, Manembo-Nembo, Bitung (SG-A) and Bahoi, Likupang Barat (SG-B) waters, were extracted with methanol and solutions were prepared in a concentration series. RESULTS: Extracts of the seagrass E. acoroides (L.f.) Royle cultivated in different areas have different phytochemical constituents and SOD activities. The secondary metabolites of phenols, flavonoids, and steroids contained in the ethyl acetic extracts of E. acoroides were linearly correlated with their antioxidant activity, whichexhibited an IC(50) of 7 ppm. CONCLUSION: E. acoroides (L.f.) Royle samples cultivated in the two areas contained different phytochemical constituent profiles, indicating an effect of environmental factors, and both can be used as potential natural sources of antioxidant compounds.